Bacterial membrane vesicles from Acinetobacter baumannii induced by ceftazidime are more virulent than those induced by imipenem. Issue 1 (31st December 2020) - Chiu, Chun-Hsiang; Lee, Yi-Tzu; Lin, Yu-Chun; Kuo, Shu-Chen; Yang, Ya-Sung; Wang, Yung-Chih; Liu, Yu-Han; Lin, Jung-Chung; Chang, Feng-Yee; Chen, Te-Li
ABSTRACT: Patients with Acinetobacter baumannii bacteremia treated with antipseudomonal cephalosporins showed higher 14-day mortality than patients treated with antipseudomonal carbapenems. We hypothesized that the bacterial membrane vesicles (BMVs) induced by antipseudomonal cephalosporins are more virulent than BMVs induced by antipseudomonal carbapenems. To simulate the clinical condition with inadequate antimicrobial treatment, carbapenem-resistant A. baumannii was treated with ceftazidime (an antipseudomonal cephalosporin) or imipenem (an antipseudomonal carbapenem) at 1/2 the minimum inhibitory concentration. BMVs and BMV-carried lipopolysaccharide were measured by nanoparticle tracking analysis and western blotting, respectively. Cytokine expression in RAW264.7 macrophages or mice serum induced by the BMVs was determined by ELISA, fluorescent bead-based immunoassay or western blotting. The virulence of the BMVs was assessed in mice. Liquid chromatography tandem-mass spectrometry was used to determine the protein contents of the BMVs. We found that ceftazidime induced a higher number of BMVs (CAZ-BMV), which carried more LPS, and induced higher expression levels of iNOS, IL-1β, and IL-6 in macrophages, higher expression of many cytokines in mice, more neutrophil infiltration in lung interstitium, and higher mortality in mice than imipenem-induced BMVs (IMP-BMV). When adjusted to same amount of LPS, CAZ-BMV still led to higher mortality than IMP-BMV. Proteomic analysis revealed different protein contents in CAZ-BMV and IMP-BMV. In conclusion, A. baumannii BMVs induced by ceftazidime are more virulent than BMVs induced by imipenem.